2020
DOI: 10.3390/genes11020206
|View full text |Cite
|
Sign up to set email alerts
|

Biosystem Analysis of the Hypoxia Inducible Domain Family Member 2A: Implications in Cancer Biology

Abstract: The expression of HIGD2A is dependent on oxygen levels, glucose concentration, and cell cycle progression. This gene encodes for protein HIG2A, found in mitochondria and the nucleus, promoting cell survival in hypoxic conditions. The genomic location of HIGD2A is in chromosome 5q35.2, where several chromosomal abnormalities are related to numerous cancers. The analysis of high definition expression profiles of HIGD2A suggests a role for HIG2A in cancer biology. Accordingly, the research objective was to perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…The expression dataset is freely available at Gene Expression Omnibus, accession number GSE145935. To confirm a robust response to hypoxia was induced, the dataset was interrogated to identify a comprehensive panel of published hypoxia-inducible genes [ 22 , 23 , 24 ], as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The expression dataset is freely available at Gene Expression Omnibus, accession number GSE145935. To confirm a robust response to hypoxia was induced, the dataset was interrogated to identify a comprehensive panel of published hypoxia-inducible genes [ 22 , 23 , 24 ], as shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it increased in the liver and spleen tissue (increased hypoxia) due to the rapid proliferation of tissue, while in healthy mice, the expression of this gene in the bone marrow and spleen increased but it decreased in the liver. Finally, they found that HIGD2A gene expression increased in DLBCL cells and decreased in nodal marginal lymphoma (NMZL) [ 82 ].…”
Section: Quercetin and Lymphomasmentioning
confidence: 99%
“…Moreover, the silencing of HIGD2A alters the viability of DLD1 colon adenocarcinoma cells, indicating that silencing HIGD2A induces death in cancer cells, suggesting a role for HIG2A in cell cycle regulation and a potential target in cancer therapy [ 16 ]. Remarkably, DNA methylation and mRNA expression in the HIGD2A gene showed significant alterations in various cancers [ 17 ]. The correlation between high HIGD2A expression and poor patient survival is significant for hepatocellular carcinoma, cutaneous melanoma, endometrial carcinoma, and uveal melanoma [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, DNA methylation and mRNA expression in the HIGD2A gene showed significant alterations in various cancers [ 17 ]. The correlation between high HIGD2A expression and poor patient survival is significant for hepatocellular carcinoma, cutaneous melanoma, endometrial carcinoma, and uveal melanoma [ 17 ]. All the above-presented studies suggest a role for HIG2A in mitochondrial physiology and cancer biology.…”
Section: Introductionmentioning
confidence: 99%